2016
DOI: 10.1246/cl.151061
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Activity of Carbon Nitride Modified with a Ruthenium(II) Complex Having Carboxylic- or Phosphonic Acid Anchoring Groups for Visible-light CO2 Reduction

Abstract: Semiconducting C 3 N 4 powder modified with a catalytic Ru(II) complex having carboxylic acid groups as anchors showed higher activity for CO 2 reduction into HCOOH under visible light ( > 400 nm) at the initial stage of the reaction, whereas an analogue anchored with phosphonic acid groups exhibited higher stability.Photocatalytic reduction of CO 2 into energy-rich chemicals has long been studied as an important half cycle of artificial photosynthesis.110 CO 2 reduction using illuminated semiconductor particl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 32 publications
1
44
0
Order By: Relevance
“…The selectivity of HCOOH exceeds 80% . A similar result was also reported that the phosphonic acid groups are efficient in photocatalytic CO 2 reduction . The binuclear ruthenium complex can bind robustly with carbon nitride in basic aqueous solution and form a Z‐Scheme heterojunction .…”
Section: Single Atomssupporting
confidence: 60%
See 1 more Smart Citation
“…The selectivity of HCOOH exceeds 80% . A similar result was also reported that the phosphonic acid groups are efficient in photocatalytic CO 2 reduction . The binuclear ruthenium complex can bind robustly with carbon nitride in basic aqueous solution and form a Z‐Scheme heterojunction .…”
Section: Single Atomssupporting
confidence: 60%
“…[106] A similar result was also reported that the phosphonic acid groups are efficient in photocatalytic CO 2 reduction. [138] The binuclear ruthenium complex can bind robustly with carbon nitride in basic aqueous solution and form a Z-Scheme heterojunction. [139,140] These two ruthenium metals have two different effects: one is the photosensitizing unit to form the Z-Scheme with carbon nitride and the other is Adv.…”
Section: Metal Complexesmentioning
confidence: 99%
“…[48] DMF undergoes decompositiond uring photocatalytic reactionm ore or less, generating formic acid whereas DMA does not. [23][24][25][26][27][28][30][31][32] Therefore, TEOA musth ave acted as ah ole scavenger in this case. The hybrid gave rise to appreciable CO formationw ith at urnover number (TON CO )o f 27 based on RuRe used after 5h irradiation( entry 1).…”
Section: Resultsmentioning
confidence: 87%
“…For the development of artificial photosynthetic schemes, variousm etal complexes [1][2][3][4][5][6][7][8][9][10][11][12][13] and semiconductors, [14][15][16][17][18][19] as well as their hybrids, [20][21][22][23][24][25][26][27][28] have been examined as photocatalystsf or CO 2 reduction. For the development of artificial photosynthetic schemes, variousm etal complexes [1][2][3][4][5][6][7][8][9][10][11][12][13] and semiconductors, [14][15][16][17][18][19] as well as their hybrids, [20][21][22]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation